2008 IEEE/RSJ International Conference on Intelligent Robots and Systems 2008
DOI: 10.1109/iros.2008.4650934
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental cooperative telemanipulation between Germany and Japan

Abstract: The video shows an intercontinental cooperative telemanipulation task, whereby the operator site is located in Munich, Germany and the teleoperator site in Tsukuba, Japan. The human operator controls a remotely located teleoperator, which performs a task in the remote environment. Hereby the human operator is assisted by another person located at the remote site. The task consists in jointly grasping an object, moving it to a new position and finally releasing it, see Fig. 1. Fig. 1. Cooperative telemanipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Hence, the round-trip time delay needs to be known, which poses a limitation compared to the original wave variable approach where the exact knowledge is not required. Recent telepresence experiments between Germany and Japan over the Internet, however, showed that the time delay even over this long-distance interconnection can be considered constant [20]. Additionally, the roundtrip time delay is rather simple to measure using time-stamps.…”
Section: L Ocal Computation Of Wave Variablesmentioning
confidence: 99%
“…Hence, the round-trip time delay needs to be known, which poses a limitation compared to the original wave variable approach where the exact knowledge is not required. Recent telepresence experiments between Germany and Japan over the Internet, however, showed that the time delay even over this long-distance interconnection can be considered constant [20]. Additionally, the roundtrip time delay is rather simple to measure using time-stamps.…”
Section: L Ocal Computation Of Wave Variablesmentioning
confidence: 99%
“…Many telerobotics research groups are rushing to explore this exciting avenue, but the communication model typically used is still that of pre-internet point-to-point networks. It is common for each teleoperation system to be programmed with the IP address of its remote partners, a practice with limited flexibility for locating users at multiple addresses [1][2][3]. Furthermore, there are no established protocols for locating remote robots or standard formats for exchanging telerobotic control data.…”
Section: Introductionmentioning
confidence: 99%